Kepatuhan Diet Penderita Diabetes Mellitus di Wilayah Kerja Puskesmas Trucuk 1 - Supardi Supardi; Marwanti Marwanti; Erika Karunia Putri; Chori Elsera; Mawardi Mawardi; Agus Murtana; Ambar Winarti (Universitas Muhammadiyah Klaten, 2025)
Background: Dietary adherence plays a very important role for people with DM, if someone who cannot manage a diet with 3j settings (schedule, type and amount) it can cause the patient to experience an increase in blood sugar levels. According to the World Health Organization (WHO) there are about 422 million people worldwide suffering from diabetes. Objectives of the Study: The purpose of this study was to determine the description of dietary compliance of patients with Diabetes Mellitus at Trucuk 1 Health Center. Research Methods: This type of research is quantitative research with descriptive correlation research design. The sample used in this study was 93 respondents. The sampling technique used in this study was purposive sampling. The instrument used was a questionnaire. Research Results: The results of the study obtained compliance with the number of respondents' diets in the compliant category as many as 65 (69.9%), the type of diet of respondents in the compliant category as many as 81 (87.1%), the respondent's diet schedule in the compliant category as many as 70 (75.3%), most of whom were female, totaling 51 respondents, elementary school education 21 respondents, trader jobs 20 respondents. Conclusion: It can be concluded that the results of the research compliance The number of respondents' diets in the compliant category was 65 (69.9%), the type of diet of respondents in the compliant category was 81 (87.1%), the respondents' diet schedule in the compliant category was 70 (75.3%).